Examining the Bone Bruise Patterns in Multiligament Knee Injuries With Peroneal Nerve Injury. Issue 6 (May 2022) - Moran, Jay; Schneble, Christopher A.; Katz, Lee D.; Fosam, Andin; Wang, Annie; Li, Don T.; Kahan, Joseph B.; McLaughlin, William M.; Jokl, Peter; Hewett, Timothy E.; LaPrade, Robert F.; Medvecky, Michael J.
Background: Tibiofemoral bone bruise patterns seen on magnetic resonance imaging (MRI) are associated with ligamentous injuries in the acutely injured knee. Bone bruise patterns in multiligament knee injuries (MLKIs) and particularly their association with common peroneal nerve (CPN) injuries are not well described. Purpose: To analyze the tibiofemoral bone bruise patterns in MLKIs with and without peroneal nerve injury. Study Design: Case series; Level of evidence, 4. Methods: We retrospectively identified 123 patients treated for an acute MLKI at a level 1 trauma center between January 2001 and March 2021. Patients were grouped into injury subtypes using the Schenck classification. Within this cohort, patients with clinically documented complete (motor and sensory loss) and/or partial CPN palsies on physical examination were identified. Imaging criteria required an MRI scan on a 1.5 or 3 Tesla scanner within 30 days of the initial MLKI. Images were retrospectively interpreted for bone bruising patterns by 2 board-certified musculoskeletal radiologists. The location of the bone bruises was mapped on fat-suppressed T2-weighted coronal and sagittal images. Bruise patterns were compared among patients with and without CPN injury. Results: Of the 108 patients with a MLKI who met the a priori inclusion criteria, 26 (24.1%) were found to have a CPN injury (N = 20 complete; N = 6 partial) on physical examination. For CPN-injured patients, the most common mechanism of injury was high-energy trauma (N = 19 [73%]). The presence of a grade 3 posterolateral corner (PLC) injury (N = 25; odds ratio [OR], 23.81 [95% CI, 3.08-184.1]; P = .0024), anteromedial femoral condyle bone bruising (N = 24; OR, 21.9 [95% CI, 3.40-202.9]; P < .001), or a documented knee dislocation (N = 16; OR, 3.45 [95% CI, 1.38-8.62]; P = .007) was significantly associated with the presence of a CPN injury. Of the 26 patients with CPN injury, 24 (92.3%) had at least 1 anteromedial femoral condyle bone bruise. All 20 (100%) patients with complete CPN injury also had at least 1 anteromedial femoral condyle bone bruise on MRI. In our MLKI cohort, the presence of anteromedial femoral condyle bone bruising had a sensitivity of 92.3% and a specificity of 64.6% for the presence of CPN injury on physical examination. Conclusion: In our MLKI cohort, the presence of a grade 3 PLC injury had the greatest association with CPN injury. Additionally, anteromedial femoral condyle bone bruising on MRI was a highly sensitive finding that was significantly correlated with CPN injury on physical examination. The high prevalence of grade 3 PLC injuries and anteromedial tibiofemoral bone bruising suggests that these MLKIs with CPN injuries most commonly occurred from a hyperextension-varus mechanism caused by a high-energy blow to the anteromedial knee.